Optimization of the Transesterification Process of Palm Oil using Ultrasound-based Technique - Ramírez Sanabria, Alfonso Enrique; López, Lizbeth Lorena; Orozco, Mara Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper shows the results in the transesterification process on high oleic palm oil using the sonication –US- technique in combination with heterogeneous catalysts. The effect was evaluated separately from the US assistance and the catalyst (TiO2, CaO, MgCO3, Na2CO3 and K2CO3). Subsequently, the biodiesel obtained using the combination of US and catalysts was evaluated and optimal performances are achieved when using this combination, but it is Na2CO3 that provides the best results, generating a 71% conversion at 12h and in a 1:6 oil:alcohol ratio.